PENGARUH AGAMA TERHADAP PERKAWINAN - Fadjar, A. Mukti (Jurnal Bestari, 1991)
In many cases, marriages sometime bring about so many problems. It goes without saying, since the issue of marriages involve several aspects. those aspects are not only in the case of social and religion, but they are also in the case of law treatment. then, who is in charge of solving themarital problem when a marriage is comitted by people whose twi different religions? Besides, what are the rules which can be employed?